Social modulation of brain monoamine levels in zebrafish - Teles, Magda (2013)
In social species animals tend to adjust their social behaviour according to the available social information in the group, in order to optimize and improve their one social status. This changing environment requires for rapid and transient behavioural changes that relies primarily on biochemical switching of existing neural networks. Monoamines and neuropeptides are the two major candidates to mediate these changes in brain states underlying socially behavioural flexibility. In the current study we used zebrafish (Danio rerio) males to study the effects of acute social interactions on rapid regional changes in brain levels of monoamines (serotonin and dopamine). A behavioural paradigm under which male zebrafish consistently express fighting behaviour was used to investigate the effects of different social experiences: winning the interaction, losing the interaction, or fighting an unsolved interaction (mirror image). We found that serotonergic activity is significantly higher in the telencephalon of winners and in the optic tectum of losers, and no significant changes were observed in mirror fighters suggesting that serotonergic activity is differentially regulated in different brain regions by social interactions. Dopaminergic activity it was also significantly higher in the telencephalon of winners which may be representative of social reward. Together our data suggests that acute social interactions elicit rapid and differential changes in serotonergic and dopaminergic activity across different brain regions.